Can Implementing New Services Organization Models to Better Meet the Needs of Young People Bring About Practice Changes? Analysis of an Experiment in Québec - N. Touati; I. Ruelland; L. Rodriguez del Barrio; M. Bouchard; K. Beaulieu; I. Courcy (SAGE Publishing, 2024)
The research question addressed in this article is: Can implementing new services organization models to better meet the needs of young people bring about practice changes? More precisely, we examine the effects of a new model called Aire Ouverte (AO) which is implemented gradually across Quebec since 2019. This new model involves public sector and community organizations. To grasp practices' change, we use cultural historical activity theory (CHAT) and employ a qualitative approach. Beyond a precise description of work activities, we gained an inside view of how the actors involved represented their practice and context. Our results show that practice changes seen by actors are in line with the object of the intervention, that is, responding rapidly to the expressed needs of young people. The development of new tools, flexible functioning, strengthening of interprofessional and intersectoral collaboration, involvement of young people in decision-making, all should contribute to improving response to their needs. This being said, a critical look at practice changes reveals a challenge in aligning the design and objective of AO with the needs of some young people. We noted also a poor alignment of effective collaborative practices between levels of care and the practices sought from intersectoral collaboration.